Accommodate or Reject: The Role of Local Communities in the Retention of Health Workers in Rural Tanzania - Nathanael Sirili; Daudi Simba; Joseph M Zulu; Gasto Frumence; Moses Tetui (Kerman University of Medical Sciences, 2022)
Background  While over 70% of the population in Tanzania reside in rural areas, only 25% of physicians and 55% of nurses serve these areas. Tanzania operates a decentralised health system which aims to bring health services closer to its people through collaborative citizen efforts. While community engagement was intended as a mechanism to support the retention of the health workforce in rural areas, the reality on the ground does not always match this ideal. This study explored the role local communities in the retention of health workers in rural Tanzania. Methods  An exploratory qualitative study was completed in two rural districts from the Kilimanjaro and Lindi regions in Tanzania between August 2015 and September 2016. Nineteen key informant interviews (KIIs) were conducted with district health managers, local government leaders, and health facility in-charges. In addition, three focus group discussions (FGDs) were conducted with 19 members of the governing committees of three health facilities from the two districts. Data were analysed using the thematic analysis technique.Results  Accommodation or rejection were the two major ways in which local communities influenced the quest for retaining health workers. Communities accommodated incoming health workers by providing them a good reception, assuming responsibility for resolving challenges facing health facilities and health workers, linking health workers to local communities and promoting practices that placed a high value on health workers. On the flip side, communities could also reject health workers by openly expressing lack of trust and labelling them as 'foreigners,' by practicing cultural rituals that health workers feared and discrimination based on cultural differences.Conclusion  Fostering good relationships between local communities and health workers may be as important as incentives and other health system strategies for the retention of health workers in rural areas. The role communities play in rural health worker retention is not sufficiently recognized and is worthy of further research.